OXIDATIVE STRESS BIOMARKERS OF EXPOSURE TO DELTAMETHRIN IN RAINBOW TROUT FRY (Oncorhynchus mykiss) - Yonar, Serpil Mise; Sakin, Fatih; Yonar, M. Enis; Ispir, Unal; Kirici, Muammer (Parlar Scientific Publications (P S P), 2011)
Deltamethrin (DM) is a widely used pesticide based on pyrethroids, and is reported to be extremely toxic to fish species. We investigated the effect of DM concentrations (0.010, 0.0125 and 0.0250 mu g/L) on antioxidants in rainbow trout, Oncorhynchus mykiss, using standard laboratory conditions. 24 h exposure caused whole body induction of various antioxidant enzymes and nonenzymatic antioxidants. Results showed that DM significantly (p<0.05) increased malondialdehyde (MDA) levels. Catalase (CAT) activity decreased in all experimental groups. Glutathione (GSH) was significantly (p<0.05) increased in the group with DM concentration of 0.0250 mu g/L DM for 24 h. The activity of glutathione peroxidase (GSH-Px) was found to be statistical significantly (p<0.05) decreased in all other experimental groups except the 0.010 mu g/L DM treated group. The parameters studied in this investigation can also be used as biomarkers of exposure to DM. It is suggested that appropriate ecotoxicological risk assessments should be made wherever DM is proposed for use in pest control activities.
Keywords: Deltamethrin; pesticide; rainbow trout; oxidative stress; antioxidant system